Feasibility Study of Machines Addition in CV. XYZ - Astrid Wahyu Adventri Wibowo; Tri Wisudawati (OPSI, 2023)
CV. XYZ is a belt-producing MSME located in Surakarta. The problems faced by CV. XYZ is the unavailability of product variations, or it can be said that these MSMEs do not yet have various product differentiations. Coupled with productivity at CV. XYZ is still bad. The workers use manual tools and the belts are perforated using nails and hammers. Based on these problems, this study aims to help CV. XYZ determines the best investment alternatives in order to maximize profits. There are 2 investment alternatives offered to increase product differentiation CV. XYZ. The first alternative (A1) is to add a pattern-making machine and replace a belt-punching tool, while the second alternative (A2) is to invest in adding a motif-making machine only. In this study, several methods were used, namely Pay Back Period (PBP), Net Present Value (NPV), Internal Rate of Return (IRR), and Profitability Index (PI). Recommendations are given to CV. XYZ is the second alternative (A2), which is investing in the addition of a pattern-making machine.